Doing E‐Business in France: Drivers of Online Trust in Business‐to‐Consumer Websites. Issue 4 (May 2014) - Bartikowski, Boris; Singh, Nitish
<x xml:space="preserve">Abstract</x> How can online marketers improve the level of trust among their consumers in order to ensure greater satisfaction with the services offered by their websites? In the absence of a detailed understanding of which website elements drive trust online, many online marketers are missing important opportunities that can make the difference between success and failure in selling and servicing online. Since France is among the largest online markets worldwide, an empirical analysis of the content of 206 websites from 11 business categories that target French consumers offers practical guidance to business‐to‐customer (B2C) marketers who strive to improve the level of online trust. The study's results provide a comprehensive set of 15 perceptual drivers of online trust with operational examples. Integrating these elements in website design may increase site credibility and facilitate transactions. The most salient trust drivers are related to brand reputation, layout design, content quality, expertise, and navigation. Depiction of cultural markers (language, typical colors, symbols, country references) is another key driver of online trust in France. Online retailers, particularly those targeting French markets, may use the study's findings to design more trusted websites or to benchmark their online trust creation capabilities. © 2014 Wiley Periodicals, Inc.